2016
DOI: 10.1039/c6rp00101g
|View full text |Cite
|
Sign up to set email alerts
|

Can they succeed? Exploring at-risk students' study habits in college general chemistry

Abstract: A well-established literature base identifies a portion of students enrolled in post-secondary General Chemistry as at-risk of failing the course based on incoming metrics. Learning about the experiences and factors that lead to this higher failure rate is essential toward improving retention in this course. This study examines the relationship between study habits and academic performance for at-risk students in General Chemistry. Students who were in the bottom quartile of SAT math scores were identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 13 publications
3
47
0
1
Order By: Relevance
“…Finally, help-seeking items for achieving all goals had adequate factor loadings. The finding coincided with the previous study results that at-risk college students tend to seek help from others when they encounter difficult problems, and that if the students cannot receive direct help from others, they ignore those problems (Ye et al., 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, help-seeking items for achieving all goals had adequate factor loadings. The finding coincided with the previous study results that at-risk college students tend to seek help from others when they encounter difficult problems, and that if the students cannot receive direct help from others, they ignore those problems (Ye et al., 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Higher education researchers have long investigated at-risk freshmen’s past and current factors such as background characteristics (e.g., socioeconomic status and minority group membership), individual characteristics (e.g., emotional, psychological, or behavioral problems), and environmental factors (e.g., college tuition and advisor support; Gray, 2013; Horton, 2015; Ye, Shuniak, Oueini, Robert, & Lewis, 2016). For example, Demetriou and Schmitz-Sciborski (2011) investigated factors, which have been widely studied over 30 years in college retention studies.…”
Section: Past and Current Factors Related To At-risk Freshmenmentioning
confidence: 99%
“…However, our findings agree with the work of Felicilda‐Reynaldo et al (), who found that anatomy was one of the nursing prerequisite courses most commonly associated with rote memorization and that flashcards were the most common strategy for that memorization. Furthermore, Ye et al () demonstrated with undergraduates in chemistry that this rote memorization was associated with lower final grades, lower metacognitive skills, and poorer affective traits (e.g., self‐efficacy). Hartwig and Dunlosky () in their survey of introductory psychology students also found a distinction in student reports of self‐testing versus flashcard use.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The areas of CER could include but are not limited to the following: laboratory learning, 4-7 pedagogy, 8 chemistry concepts and knowledge construction, [9][10][11][12] assessment, [13][14][15] technologies (broadly defined), [16][17][18] curriculum development, 19,20 emerging areas, 21,22 attitudes and beliefs (affect), [23][24][25][26] and equity, diversity, and inclusion. [27][28][29] Once an issue and research questions have been established, educational research is guided by one or more theoretical frameworks. A theoretical framework is a "system of ideas, aims, goals, theories and assumptions about knowledge, how research should be carried out, and how research should be reported."…”
Section: What Is Cer?mentioning
confidence: 99%